Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $X$ and $Y$ are independent binomial random variables with parameter $n$ and $p$. Their sum is denoted by $Z$. How do I prove :

$$ P(X=k\mid Z=m) = {n \choose k}{n \choose m-k}\biggm/ {2n \choose m} $$

share|cite|improve this question

1 Answer 1

As $X$ and $Y$ are independent, we have $Z \cong \mathrm{Binomial}(2n, p)$, hence $$ P(Z = m) = \binom{2n}m p^m(1-p)^{2m-p} $$ Moreover \begin{align*} P(X= k, Z=m) &= P(X=k, X+Y=m)\\ &= P(X=k, Y = m-k)\\ &= P(X=k)P(Y=m-k)\\ &=\binom nk p^k(1-p)^{n-k}\binom n{m-k}p^{m-k}(1-p)^{n-m+k}\\ &= \binom nk\binom n{m-k} p^m (1-p)^{2n-m} \end{align*} And therefore $$ P(X = k \mid Z= m) = \frac{P(X=k,Z=m)}{P(Z=m)} = \frac{\binom nk\binom n{m-k}}{\binom{2n}m} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.